Integrating Thermo-Ombroclimatic Indicators into Sustainable Olive Management: A Pathway for Innovation and Education - José Carlos Piñar-Fuentes; Juan Peña-Martínez; Ana Cano-Ortiz (Agriculture, 2024)
The study explores the integration of thermo and ombroclimatic bioindicators into sustainable agricultural practices, focusing on olive production in the Mediterranean. Given the increasing challenges posed by climate change, the study highlights the critical role of bioindicators in optimizing crop resilience and yield. Using data from the CHELSA model and long-term olive production records, the research identifies the impact of key climatic factors, such as temperature and precipitation, on olive yield variability. Principal component analysis (PCA) revealed that geographical location, precipitation, and thermal extremes significantly influence productivity. Furthermore, a multiple linear regression model confirmed the ombroclimatic index (Io) as a strong predictor of yield, emphasizing the necessity of balanced climatic conditions. The findings advocate for the integration of bioclimatic principles into agricultural training programs, promoting a holistic approach to crop management. Ultimately, the study underscores the need for informed decision-making and adaptive practices to ensure sustainable agricultural production under varying climatic conditions. This research provides a framework for future studies aiming to enhance crop resilience and address climate challenges, suggesting a pathway towards an innovative, sustainable agricultural model.